Characteristics of goal attacks games team qualifications - Andrii Pertsukhov (Kharkiv State Academy of Physical Culture, 2016)
Purpose: of this paper is to determine quantitative and qualitative indices of the resultive attacking actions in the games of teams-participants of World Championship 2014. Material & Methods: analysis of the scientific-methodical literature, registration of technique-tactic action, methods of mathematical statistics. Research of the competitive action was realized with the teams-participants of World Championship 2014. Results: the article represents the indices characterized goal attacks in the fames of World Championship 2014. Conclusions: according to the research it was determined that in case during attack since the moment of possession of the ball the team mares 6-7 and more passes and expends more than 9 seconds the probability to score the goal comes to minimum.